2022
DOI: 10.3389/fphys.2022.927794
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin attenuates tubulointerstitial fibrosis in diabetic kidney disease by inhibiting YAP expression and nuclear translocation

Abstract: The activation of Yes-associated protein (YAP) pathway is mutually causal with the increase of extracellular matrix (ECM) stiffness. Polydatin (PD) has been proved to have anti-fibrosis effect in diabetic kidney disease (DKD), but it is still a mystery whether PD participates in YAP-related mechano-transduction. Therefore, this study intends to solve the following two problems: 1) To construct an in vitro system of polyacrylamide hydrogels (PA gels) based on the true stiffness of kidneys in healthy and DKD rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Polydatin (PD) is a natural active ingredient in the thuja family of plants. A study demonstrated that the mechanism of PD inhibiting YAP activity and nuclear translocation is similar to VP, but its function in reducing α‐SMA expression and collagen I deposition was more pronounced compared with VP 310 . In the activated Hippo signaling pathway 14‐3‐3ζ can bind to YAP/TAZ in the cytoplasm and contributes to YAP/TAZ degradation.…”
Section: Yap/taz and Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Polydatin (PD) is a natural active ingredient in the thuja family of plants. A study demonstrated that the mechanism of PD inhibiting YAP activity and nuclear translocation is similar to VP, but its function in reducing α‐SMA expression and collagen I deposition was more pronounced compared with VP 310 . In the activated Hippo signaling pathway 14‐3‐3ζ can bind to YAP/TAZ in the cytoplasm and contributes to YAP/TAZ degradation.…”
Section: Yap/taz and Fibrosismentioning
confidence: 99%
“…A study demonstrated that the mechanism of PD inhibiting YAP activity and nuclear translocation is similar to VP, but its function in reducing α‐SMA expression and collagen I deposition was more pronounced compared with VP. 310 In the activated Hippo signaling pathway 14‐3‐3ζ can bind to YAP/TAZ in the cytoplasm and contributes to YAP/TAZ degradation. It was found that when in a mouse model of acute kidney injury with 14‐3‐3ζ overexpression, the expression of fibrosis‐related proteins was downregulated and interstitial fibrosis was alleviated.…”
Section: Yap/taz and Fibrosismentioning
confidence: 99%
“…To assess the suggested model's performance on bigger and more varied datasets, more investigation is required. Chen et al used a convolutional neural network (CNN) model to apply deep learning to the detection of CKD [4]. On a benchmark dataset, the suggested CNN model produced cutting-edge results, showcasing the potential of deep learning for CKD detection.…”
Section: Related Workmentioning
confidence: 99%
“… 11 In the Hippo pathway, LATS1 and MST1 are protein kinases which, on activation, stimulate LATS1 phosphorylation of important downstream effectors such as TAZ and YAP. 12 In particular, as a key factor in the pathway, YAP controls the size of organs by mediating epithelial–mesenchymal transformation and regulating cell contact inhibition as well as cell apoptosis, differentiation, and proliferation. It has been previously shown that targeting the activation of YAP in human cancer was of interest for the development of chemotherapeutic drugs.…”
Section: Introduction To the Hippo/yap Pathwaymentioning
confidence: 99%
“…Moreover, YAP’s functions in diabetic vascular ECs were also explored, with results showing that inhibiting YAP decreased tube formation, cell proliferation, and cell migration under hypoxic conditions. 12 , 17 Therefore, YAP is a key regulator of tumor growth and invasion while being an important link in glucose metabolism as its activation regulates gluconeogenesis and hence glucose tolerance levels. 27 The localization of YAP, which is the nuclear sensor of the Hippo pathway, is indicative of the activation state of the Takeda G-coupled receptor 5 (TGR5), and as such, YAP is important to determine the intestinal structure as well as the fate of different cells, particularly during epithelial regeneration.…”
Section: Introduction To the Hippo/yap Pathwaymentioning
confidence: 99%